2017
DOI: 10.1002/acp.3339
|View full text |Cite
|
Sign up to set email alerts
|

Selective Association Between Tetris Game Play and Visuospatial Working Memory: A Preliminary Investigation

Abstract: SummaryRecent experimental and clinical research has suggested that Tetris game play can disrupt maladaptive forms of mental imagery because Tetris competes for limited cognitive resources within visuospatial working memory (WM) that contribute to imagery. Whether or not Tetris performance is selectively associated with visuospatial WM remains to be tested. In this study, young adults (N = 46) completed six standardized measures indexing verbal and non‐verbal reasoning, verbal and visuospatial short‐term memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 58 publications
5
42
0
1
Order By: Relevance
“…Indeed, the five proposed games, albeit focusing on different cognitive domains, relied on visual-spatial competence as they required participants to: i) detect the orientation of a stimulus in space (Disillusion, Lost in Migration), ii) match together (Disillusion) or recognize (Tidal Treasure, Speed Match) visually presented figures that could differ in shape and color, iii) solve arithmetic operations contained in drops that moved vertically on the computer screen and were distributed in space (Raindrops), and iv) maintain in working memory the shapes and colors of visual stimuli (Tidal Treasure, Speed Match). This hypothesis is in line with the notion that computer games heavily tax visual-spatial working-memory [49][50][51] and that the benefits of games like Tetris on mental health are likely proxied by occupying visual-spatial working memory [64][65][66][67] . In keeping with it, previous research showed that visual-spatial abilities are enhanced by video-and computer-game playing, even after a few months of training 50 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Indeed, the five proposed games, albeit focusing on different cognitive domains, relied on visual-spatial competence as they required participants to: i) detect the orientation of a stimulus in space (Disillusion, Lost in Migration), ii) match together (Disillusion) or recognize (Tidal Treasure, Speed Match) visually presented figures that could differ in shape and color, iii) solve arithmetic operations contained in drops that moved vertically on the computer screen and were distributed in space (Raindrops), and iv) maintain in working memory the shapes and colors of visual stimuli (Tidal Treasure, Speed Match). This hypothesis is in line with the notion that computer games heavily tax visual-spatial working-memory [49][50][51] and that the benefits of games like Tetris on mental health are likely proxied by occupying visual-spatial working memory [64][65][66][67] . In keeping with it, previous research showed that visual-spatial abilities are enhanced by video-and computer-game playing, even after a few months of training 50 .…”
Section: Discussionsupporting
confidence: 79%
“…It was hypothesized that visual-spatial working memory could be improved after the training (primary outcome) for the following reasons: i) the CCT provided exercises addressing different cognitive skills but all strongly relying on visual-spatial abilities; ii) previous research found benefits in visual-related abilities from videogames [49][50][51] in the healthy population and the CCT exercises had a game-like format; iii) the CCT proposed drill-based exercises and previous research found that CCT programs mostly based on drill-based exercises produce gains in visual-spatial abilities of children with ABI. In contrast, there is more limited evidence on the benefits of CCT programs based on drill-based exercises on cognitive abilities different from visual-spatial skills in either the general population or in children and adolescents with ABI.…”
mentioning
confidence: 99%
“…The three games were chosen together for a diversity of gameplay characteristics in order to explore different demands on cognitive function, i.e. visuospatial in Tetris [22], response inhibition and attention in Fruit Ninja [24] and visual search in Candy Crush Saga.…”
Section: Gamesmentioning
confidence: 99%
“…Bei Tetris muss man nach unten fallende geometrische Figuren so rotieren, dass sie sich möglichst nahtlos auf den "Boden" mit bereits vorhandenen Figuren einfügen, eine visuospatial fordernde Aufgabe. Die Arbeitsgruppe um Emily Holmes konnte wiederholt zeigen, dass das Spielen von Tetris bei gesunden Probanden während oder direkt nach der Betrachtung eines sogenannten Traumafilms (mit visuell unangenehmen Szenen, die typischerweise im Anschluss Intrusionen auslösen) dazu führt, dass in der Woche nach dem Film weniger Intrusionen auftreten als bei verschiedenen Kontrollgruppen [26][27][28]. Erste klinische Studien mit Tetris zeigen bereits vielversprechende Ergebnisse: Wird innerhalb von 6 Stunden nach einem Verkehrsunfall [7] oder einer Notfall-Sectio [29] Tetris gespielt, treten im Vergleich zu Kontrollgruppen weniger Intrusionen im Hinblick auf die jeweiligen traumatischen Ereignisse auf.…”
Section: Visuospatiale Interventionenunclassified